GC-MS analysis of organic fractions of Chrozophora tinctoria (L.) A.Juss. and their prokinetic propensity in animal models - Sher,A. A. (2024)
Abstract Chrozophora tinctoria (L.) A.Juss. is herbaceous, monecious annual plant used traditionally to cure gastrointestinal disorders. The present study was carried out to find the bioactive compounds by Gas Chromatography-Mass Spectrometry, the acetylcholinesterase inhibitory potential acute toxicity, and emetic activity present in the ethyl acetate fraction of Chrozophora tinctoria (EAFCT) and dichloromethane fraction of Chrozophora tinctoria (DCMFCT). The compounds detected in both fractions were mostly fatty acids, with about seven compounds in EAFCT and 10 in DCMFCT. These included pharmacologically active compounds such as imipramine, used to treat depression, or hexadecanoic acid methyl ester, an antioxidant, nematicide, pesticide, hypocholesterolemic, 9,12,15-Octadecatrienoic acid, ethyl ester, (Z,Z,Z)- is used as a cancer preventive, antiarthritic, antihistaminic, hepatoprotective, insectifuge, nematicide, Pentadecanoic acid, 14-methyl-, methyl ester have antifungal, antimicrobial and antioxidant activities, 10-Octadecanoic acid, methyl ester have the property to decrease blood cholesterol, Antioxidant and antimicrobial, 1-Eicosanol is used as an antibacterial, 1-Hexadecene has antibacterial, antioxidant, and antifungal activities. Both DCMFCT and EAFCT fractions inhibited acetylcholinesterase (AChE) activity with IC50 values of 10 µg and 130 µg, respectively. Both the fractions were found to be toxic in a dose-dependent manner, inducing emesis at 0.5g onward and lethargy and mortality from 3–5 g upwards. Both the fractions combined with distilled water showed highly emetic activity. The significant increase in the number of vomits was shown by EAFCT plus distilled water which are 7.50±1.29, 7.25±3.10, and 11.75±2.22 number of vomits at 1g, 2g, and 3g/kg concentration respectively, while DCMFCT plus distilled water showed 5.25±2.22, 7.50±2.52 and 10.25±2.22 number of vomits at 1g, 2, and 3g/kg correspondingly. The antiemetic standard drug metoclopramide has a higher impact against the emesis induced by both the fractions than dimenhydrinate. Metoclopramide decreases the number of vomits caused by EAFCT to 1.00±0.00, 2.00±0.00, 4.00±1.00 at 1g, 2, and 3g/kg sequentially, while dimenhydrinate decreases the number of vomits to 1.33±0.58, 2.33±1.15, 4.33±0.58 at 1g, 2, and 3g respectively. In the same way, Metochloprimide decreases the number of emesis caused by DcmCt from 5.25±2.22, 7.50±2.52, 10.25±2.22 to 1.33±0.58, 2.33±1.1, 4.33±0.58 at 1g, 2, and 3g/kg concentrations. The present study is the first documented report that scientifically validates the folkloric use of Chrozophora tinctoria as an emetic agent.